IMPLEMENTATION OF DIVERSION TOWARDS CHILDREN WHO COMMIT CRIMINAL ACTS OF DRUG ABUSE IN DENPASAR CITY RESORT POLICE - I Komang Pandu Tanaya; Ni Wayan Ella Apryani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This study aims to determine the application of diversion for children who commit narcotics abuse in the Denpasar City Police, as well as to identify the obstacles encountered in carrying out diversion related to cases of narcotics abuse crimes committed by children in the same jurisdiction. The research method used is empirical legal research by analyzing the gaps between "das sollen" (what should be) and "das sein" (what is). The approach used is the statutory approach and the fact approach. Data collection techniques include literature search, documentation, and interviews. Furthermore, both primary and secondary data were qualitatively analyzed. The results of this study indicate that investigations into narcotics crimes committed by children in the jurisdiction of the Denpasar City Police involve asking for consideration or advice from the Community Advisor after a crime is reported or complained about. In cases of children who are in conflict with the law related to narcotics crimes during 2020, 2021, and until the end of August 2022, investigators did not make diversion efforts because the child perpetrators had repeatedly committed the same offense. Therefore, the diversion requirements were not met in accordance with the Juvenile Crime Justice System Law. However, in 2019, there was one successful case of diversion attempt. This was because it was the first time the child in conflict with the law was involved in narcotics abuse.